Perlindungan Hukum Kreditor terhadap Praktik Asset Stripping dalam Restrukturisasi Grup Perusahaan Multinasional: Studi Doktrin Cross-Border Insolvency dan Piercing the Corporate Veil - Afandono Cahyo Putranto; Fakhrul Ardiyan; Irvandi Irvandi; Riski Ari Wibowo; Diani Sadiawati (Lembaga Yasin AlSys, 2026)
Legal protection for creditors against asset stripping practices in the restructuring of multinational corporate groups has become an important issue because asset depletion by foreign parent companies can weaken creditors’ position in bankruptcy and corporate restructuring processes. This study aims to analyze the effectiveness of cross-border insolvency and the doctrine of piercing the corporate veil in providing legal protection for creditors, particularly in the context of the limitations of Law No. 37 of 2004 concerning Bankruptcy and Suspension of Debt Payment Obligations (PKPU) in regulating cross-border bankruptcy and asset stripping practices. This study uses a normative juridical method with statutory, conceptual, and functional comparative approaches to the legal systems of Indonesia, the United States, and the United Kingdom. The results show that the doctrine of piercing the corporate veil in Indonesian law has not been able to reach foreign parent companies that systematically conduct asset stripping against subsidiaries in Indonesia because of the limitations of extraterritorial jurisdiction and the absence of an adequate cross-border insolvency mechanism. In addition, the reconstruction of national bankruptcy law needs to be directed toward the adoption of the UNCITRAL Model Law on Cross-Border Insolvency 1997, the expansion of cross-border actio pauliana mechanisms, the strengthening of the doctrine of piercing the corporate veil with extraterritorial elements, and the regulation of substantive consolidation for multinational business groups. The conclusion of this study affirms that creditor protection in the restructuring of multinational corporate groups requires a hybrid regulatory model that integrates cross-border insolvency mechanisms into the Indonesian bankruptcy law system while maintaining national legal characteristics and needs. These findings provide a theoretical contribution to the development of cross-border bankruptcy law and practical implications for policymakers in strengthening creditor protection against asset stripping practices in multinational corporate structures.